The lack of PPARα exacerbated the progression of non-alcoholic steatohepatitis in mice with spleen deficiency syndrome by triggering an inflammatory response - Huang, Jiawen; Li, Jiayu; Peng, Yuan; Cui, Tianqi; Guo, Jingyi; Duan, Siwei; Zhou, Kaili; Huang, Shangyi; Chen, Jiabing; Yi, Qincheng; Qiu, Min; Chen, Tingting; et al. (Frontiers in Immunology, 2024)
Background: In addition to abnormal liver inflammation, the main symptoms of non-alcoholic steatohepatitis (NASH) are often accompanied by gastrointestinal digestive dysfunction, consistent with the concept of spleen deficiency (SD) in traditional Chinese medicine. As an important metabolic sensor, whether peroxisome proliferator activated receptor alphas (PPARα) participates in regulating the occurrence and development of NASH with SD (NASH-SD) remains to be explored.Methods: Clinical liver samples were collected for RNA-seq analysis. C57BL/6J mice induced by folium sennae (SE) were used as a SD model. qPCR analysis were conducted to evaluate inflammation and metabolic levels of mice. PPARα knockout mice (PPARα ko ) were subjected to SE and methionine-choline deficient (MCD)-diet to establish NASH-SD model. The phenotype of NASH and inflammatory indicators were measured using histopathologic analysis and qPCR as well.The abnormal expression of PPARα signaling, coupled with metabolism and inflammation were found in the results of RNA-seq analysis from clinical samples. SD mice showed more severe inflammatory response in liver evidenced by the increases of macrophage biomarkers, inflammatory factors as well as fibrotic indicators in liver. qPCR results also showed difference of PPARα between SD mice and control mice. The further evidences were found in PPARα ko mice that lack of PPARα exacerbated the phenotype of inflammatory response as well as disorder of lipid metabolism in NASH-SD mice.The abnormal NRs signaling accelerated the vicious cycle between lipotoxicity and inflammatory response in NAFLD with SD. Our results provide new evidence for nuclear receptors as potential therapeutic targets for NAFLD with spleen deficiency.